Viabilidade de agentes bacterianos como probiótico no cultivo do camarão marinho Litopenaeus vannamei - Amarante, Deborah Oliveira (2016)
Probiotics have emerged as an alternative to antibiotics in the control of pathogenic bacteria. Seeking alternatives to reduce Vibrio infections comes the use of bacteria of the genus Bacillus as prevention for the onset of diseases. The main objective of the research was to test the feasibility and efficiency of bacteria isolated from the intestinal tract of healthy shellfish such as probiotic agents in the cultivation of Litopenaeus vannamei. Were tested 17 strains of the genus Bacillus and a strain of genus Paenibacillus, of the following species: B. circulans (n = 1), B. megaterium (n = 1), B. subtilis (n = 2), B. cereus ( n = 2), Bacillus thuringiensis (n = 2), Bacillus sp. (n = 9) and P. agaridevorans (n = 1). The temperature tolerance activity tests were conducted under different concentrations viability pH and tolerance to NaCl. The susceptibility testing to antibiotics and analysis of the presence or absence of some virulence factors was performed. The inhibition test was done to pathogens in two ways: using agar plugs and through cross-striations (cross streak). The aggregation ability was observed through the glass adhesion test. In vivo experiment was performed using Litopenaeus vannamei shrimp with average weight of 10 g. The experimental design was completely at random and were supplemented as follows: Treatment A: control (no supplementation); Treatment B: a strain sprinkler; Treatment C: Bacterial mix spray; Treatment D: A Strain bioencapsulated sodium alginate; Treatment E: Bacterial mix bioencapsulated sodium alginate. The feed was offered ad libitum three times a day for 30 days. Biometrics animal was taken every 10 days. After 30 days of feeding, the shrimp were challenged against the pathogen Vibrio harveyi. Standard plate count (SPC) was performed to Vibrio and Bacillus from gut and intestinal contents before and after the infection of the system. Most of the strains showed potential for use as probiotics in shrimp farming. The final weight was statistically superior to the initial weight for treatments A, B, D and E (p <0.05). The treatments of bacteria of the genus Bacillus reduced growth of bacteria of the genus Vibrio after infection. Thus, it suggested to carry out further studies of potential probiotic strains of Bacillus sp. in the control of Vibrio, minimizing the effects of this pathogen in shrimp farming.